Numerical conformal mapping for exterior regions via the kerzman-stein kernel - Murid, A. H. M.; Nashed, M. Z.; Razali, M. R. M. (The Rocky Mountain Mathematics Consortium, Rocky Mountain Mathematics Consortium, 1998)
A simple numerical method is described for computing a conformal map from a domain exterior to a smooth Jordan curve in the complex plane onto the exterior of the unit disk. The numerical method is based on a boundary integral equation similar to the Kerzman-Stein integral equation for interior mappings. Typical examples show that numerical results of high accuracy can be obtained provided that the boundaries are smooth